2018
DOI: 10.3390/toxins10070272
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin Biosensor Based on Optical Planar Waveguide

Abstract: The research aim of this work is to develop a simple and highly sensitive optical biosensor for detection of mycotoxins. This sensor is built on a planar waveguide operating on the polarization interferometry principle, i.e., detecting a phase shift between p- and s-components of polarized light developed during the binding of analyte molecules. The operation of the proposed sensor is similar to that of a Mach–Zehnder interferometer, while its design is much simpler and it does not require splitting the wavegu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Only a few examples of antibody-based interferometric sensors for small molecules have been reported using the direct assay format. A polarization interferometer biosensor based on a planar waveguide for the detection of mycotoxins AFB 1 [216] and OTA [217] was able to detect the mycotoxins at concentrations down to ppts in a direct immunoassay format. The operating mode was similar to MZI, but the design was simpler, and the waveguide was not split into two arms.…”
Section: Interferometric Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few examples of antibody-based interferometric sensors for small molecules have been reported using the direct assay format. A polarization interferometer biosensor based on a planar waveguide for the detection of mycotoxins AFB 1 [216] and OTA [217] was able to detect the mycotoxins at concentrations down to ppts in a direct immunoassay format. The operating mode was similar to MZI, but the design was simpler, and the waveguide was not split into two arms.…”
Section: Interferometric Biosensorsmentioning
confidence: 99%
“…The operating mode was similar to MZI, but the design was simpler, and the waveguide was not split into two arms. The waveguides consisted of a thin Si 3 O 4 layer (200 nm) sandwiched between thicker SiO 2 layers (3 μm) and the light propagated in the core at an angle of 47° and experienced about 3000 [216] or 800 [217] reflections per mm. For biosensor development, a portion of the SiO 2 layer was etched, and a layer of positively charged poly-allylamine hydrochloride was deposited, followed by adsorption of protein A molecules, negatively charged, followed by immobilization of the monoclonal antibodies selective to the analyzed mycotoxin.…”
Section: Interferometric Biosensorsmentioning
confidence: 99%
“…Series of biosensing tests on detection of ochratoxin A (OTA) were carried out in direct immunoassay with specific whole antibodies immobilized electrostatically in the sensing window [65] (the immobilization protocol was described in section 2), and the results are shown in Figure 12.…”
Section: Miniaturisation Of Optical Biosensors: Planar Waveguide Biosmentioning
confidence: 99%
“…A logical continuation of this direction in biosensor development was the use of optical planar waveguide (OPW) operating as a polarization interferometer (PI) with the multiperiodic output signal proportional to the phase shift between p- and s-components of polarized light [8]. Previous attempts in this development were encouraging [9, 10]; the PI OPW devices demonstrated high refractive index sensitivity (RIS) which allows the detection of mycotoxins (aflatoxin B1, ochratoxin A, and zearalenone) in concentrations down to 0.01 ppb. During the last couple of years, the PI OPW experimental setup underwent several rounds of upgrading.…”
Section: Introductionmentioning
confidence: 99%
“…The development of fully integrated all-silicon biosensors comprising multichannel MZ interferometers with embedded avalanche LEDs as light sources, sensitive photodetectors, and microfluidic sample delivery system [1821] was the pinnacle of this direction of research and development; such highly sensitive and portable devices showed their versatility in a wide range of applications from environmental to biomedical, and suitability for in-field or point-of-care detection of analytes of interest. The proposed PI biosensor has similar sensitivity to that of MZ-based devices, but achieved with much simpler design without splitting the waveguide [810].…”
Section: Introductionmentioning
confidence: 99%